Estimativas de parâmetros genéticos para seleção precoce de clones de Eucalyptus para região com ocorrência de geadas - De Moraes, Cristiano Bueno [UNESP]; De Freitas, Talitha Casella Moreira [UNESP]; Pieroni, Gustavo Bloise; De Resende, Marcos Deon Vilela; Zimback, Léo; Mori, Edson Seizo [UNESP] (My University, 2014)
Further to increase the wood yield, is important goal of forest tree breeding the adaptation of clones through diverse environment, especially for soil and climate. Perennial tree species such as eucalypts, have a long life cycle and the frosts can occur and to be their limiting source of cultivation. The aim of the study was to determine the genetic variability and the genetic correlations between selection ages of clones cultivated in the municipality of Palma Sola, SC, Brazil, where frosts are common in the winter. A clonal trial was set up in 2008 in Palma Sola, by statistical design of randomized complete blocks considering 29 clones, six replications, six plants per plot, and 3.0m x 3.0 m spacing. The silvicultural characters of total plant height, diameter of breast height (dbh), and wood volume were evaluated through 24, 36, 48, and 60 months old. The deviance analysis and estimates of genetic parameters were based on the REML / BLUP genetic statistical procedure. Significant differences were observed for all traits in the deviance analysis. High correlations and statistically significant between characters were observed, indicating that the early selection will provide significant gains. Part of the clones USP/IPEF 64, USP/IPEF 78, USP/IPEF 52, USP/IPEF 68, and USP/IPEF 74) are potential to be used into the breeding programs and in commercial stands into the studied frost regions.
Genetic parameters of Eucalyptus clones for early selection in frost occurrence region
Keywords: Clone selection; Cold tolerance; Correlation; Improvement